A W-CDMA Zero-IF Front-End for UMTS in a 75 GHz SiGe BiCMOS Technology - Pretl, Harald; Schelmbauer, Werner; Maurer, Linus; Westermayr, H.; Weigel, Robert; Klepser, Bernd-Ulrich; Adler, Bernd; Fenk, K. (IEEE Radio Frequency Integrated Circuits Symposium, 2001)
A zero-IF front-end consisting of an I/Q down-conversion mixer, broadband I/Q-generation, fully-integrated VCO, dual-modulus prescaler, low-noise baseband buffer and blocking filter is presented. Integrated in a 75 GHz ft BiCMOS technology with 0.35 μm CMOS it draws 33 mA from a 2.7 V supply. Extremely low local-oscillator leakage of -95 dBm together with a high IIP2 of 55 dBm results in very low DC offset values of less than 20 mV at the baseband output of the IC. The presented circuit is intended for application in a highly-integrated UMTS receiver.
elib2cris::1512001600,pretl2001
Keywords: W-CDMA; Zero-IF Front-End; UMTS; SiGe BiCMOS